Innovation in repair techniques of concrete structures :proceedings of a session sponsored by the Materials Engineering Division in conjunction with the ASCE National Convention, Dallas, Texas, October 24-28, 1993 /sponsored by the Materials Engineering Division of the American Society of Civil Engineers in cooperation with the Department of Civil Engineering and Mechanics of Southern Illinois University at Carbondale ; edited by Nader Ghafoori. - Ghafoori, Nader.
Includes bibliographical references and index.